2000
DOI: 10.1128/aac.44.2.421-424.2000
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Florfenicol Resistance Genes in Escherichia coli Isolated from Sick Chickens

Abstract: Florfenicol is an antibiotic approved for veterinary use in cattle in the United States in 1996. Although this drug is not used in poultry, we have detected resistance to florfenicol in clinical isolates of avian Escherichia coli. Molecular typing demonstrated that the florfenicol resistance gene, flo, was independently acquired and is plasmid encoded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 17 publications
(16 reference statements)
8
93
1
1
Order By: Relevance
“…In the light of evidence of horizontal transfer of the DT104 antibiotic resistance gene cluster to other Typhimurium phage types or other S. enterica serovars [18], these methods appear to be no longer suitable for the specific detection of multidrug-resistant S. enterica Typhimurium DT104. Let us also mention the recently described occurrence of florfenicol resistance encoded by the floR gene on conjugative plasmids or on the chromosome of Escherichia coli isolated from cattle and poultry [17,25,53].…”
Section: Molecular Identification and Detection Methodsmentioning
confidence: 99%
“…In the light of evidence of horizontal transfer of the DT104 antibiotic resistance gene cluster to other Typhimurium phage types or other S. enterica serovars [18], these methods appear to be no longer suitable for the specific detection of multidrug-resistant S. enterica Typhimurium DT104. Let us also mention the recently described occurrence of florfenicol resistance encoded by the floR gene on conjugative plasmids or on the chromosome of Escherichia coli isolated from cattle and poultry [17,25,53].…”
Section: Molecular Identification and Detection Methodsmentioning
confidence: 99%
“…Finally, we detected the floR gene in only one isolate. Other studies have reported the presence of floR in a large number of E. coli strains from chickens and cattle (7,16,35).…”
Section: Discussionmentioning
confidence: 99%
“…Efflux systems which confer either only chloramphenicol resistance or combined resistance to chloramphenicol and florfenicol have also been described [2,3,8,17,18,32,77]. Permeability barriers and multidrug transporters only play a role in certain gram-negative bacteria [44,48].…”
Section: Resistance To Chloramphenicol and Florfenicolmentioning
confidence: 99%
“…Genes, such as pp-flo and floR -coding for membrane-associated efflux systems which export chloramphenicol and florfenicol -have been detected on a plasmid in Photobacterium damselae subsp. piscicida [33] as part of a chromosomal multiresistance gene cluster in Salmonella enterica serovars Typhimurium [3,8] and Agona [18], but also on multiresistance plasmids of E. coli [17,32,77].…”
Section: Resistance To Chloramphenicol and Florfenicolmentioning
confidence: 99%